2022
DOI: 10.29244/j.agromet.36.2.60-69
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Water Utilization through Identification of Distribution and Types of Water Harvest Infrastructure to Increase Agricultural Production, Study Case in Lampung Province

Abstract: Indonesian government has promoted the acceleration of local reservoirs development in rural areas. This development shall be integrated in agri-cultural areas to increase its production. Therefore, identification of the potential location and the type of water harvesting infrastructure are crucial to support and optimize the reservoir construction. Here, this research aims to identify the potential location distribution and the type of water harvesting infrastructure in Lampung Province. A Geographic Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This study showed that rainwater harvesting through channel reservoirs can be used as a source of irrigation in the dry season (in August and September 2017). This is in line with Rejekiningrum et al (2022a, b)…”
Section: Water Management Design Through Channel Reservoirsupporting
confidence: 89%
“…This study showed that rainwater harvesting through channel reservoirs can be used as a source of irrigation in the dry season (in August and September 2017). This is in line with Rejekiningrum et al (2022a, b)…”
Section: Water Management Design Through Channel Reservoirsupporting
confidence: 89%